Validation of Ionospheric Specifications During Geomagnetic Storms: TEC and foF2 During the 2013 March Storm Event. Issue 11 (5th November 2018) - Shim, J. S.; Tsagouri, I.; Goncharenko, L.; Rastaetter, L.; Kuznetsova, M.; Bilitza, D.; Codrescu, M.; Coster, A. J.; Solomon, S. C.; Fedrizzi, M.; Förster, M.; Fuller‐Rowell, T. J.; et al.
Abstract: To address challenges of assessing space weather modeling capabilities, the Community Coordinated Modeling Center is leading a newly established International Forum for Space Weather Modeling Capabilities Assessment . This paper presents preliminary results of validation of modeled foF2 ( F 2 layer critical frequency) and TEC (total electron content) during the first selected 2013 March storm event (17 March 2013). In this study, we used eight ionospheric models ranging from empirical to physics‐based, coupled ionosphere‐thermosphere and data assimilation models. The quantities we considered are TEC and foF2 changes and percentage changes compared to quiet time background, and the maximum and minimum percentage changes. In addition, we considered normalized percentage changes of TEC. We compared the modeled quantities with ground‐based observations of vertical Global Navigation Satellite System TEC (provided by Massachusetts Institute of Technology Haystack Observatory) and foF2 data (provided by Global Ionospheric Radio Observatory) at the 12 locations selected in middle latitudes of the American and European‐African longitude sectors. To quantitatively evaluate the models' performance, we calculated skill scores including correlation coefficient, root‐mean square error (RMSE), ratio of the modeled to observed maximum percentage changes (yield), and timing error. Our study indicates that average RMSEs of foF2 range from about 1 MHz to 1.5 MHz. The average RMSEs of TEC are between ~5 and ~10 TECU (1 TEC Unit = 10 16  el/m 2 ). dfoF2[%] RMSEs are between 15% and 25%, which is smaller than RMSE of dTEC[%] ranging from 30% to 60%. The performance of the models varies with the location and metrics considered. Key Points: foF2/TEC and foF2/TEC changes during a storm predicted by eight ionosphere models were compared with GIRO foF2 and GPS TEC measurements Skill scores (e.g., correlation coefficient, RMSE, yield, and timing error) were calculated Model performance strongly depends on the quantities considered, the type of metrics used, and the location considered